Systems analysis and design - Shelly, Gary B. (Thomson Course Technology, 2008)
Building on the proven pedagogy of its predecessors, with an increased focus on object modeling and project management, Systems Analysis and Design, Seventh Edition presents a clear introduction to systems analysis and design. Students will find concepts easy-to-understand through the clear writing style and full-color figures that illustrate current technology and trends. Examples and cases are drawn from actual systems projects that enable students to learn in the context of solving problems, much like the ones they will encounter on the job. This approach, combined with motivating tools such as the SCR Associates interactive Web-Based Case Study, Systems Analyst's Toolkit, the Student Study Tool on CD-ROM, and more, makes Systems Analysis and Design, Seventh Edition a wise and exciting choice for your introductory systems analysis and design class